Benefits of Community: Students-as-Partners Work by an Undergraduate Student, a Graduate Student, and a Faculty Member (Teaching and Learning Inquiry, 2022)
Unfamiliarity and uncertainty can be disorienting, but when provided space to collectively navigate such challenges, opportunities arise for novel ways of engaging, collaborating, and navigating in our varied communities—including those in higher education. This article builds on previous students-as-partners (SaP) research by describing a collaborative investigation into teaching and learning and how the three authors of this article (an undergraduate student, a graduate student, and a faculty member) worked together to address challenges in their personal and professional spheres. We recount exploratory mixed-methods work that highlights the natural evolution of a unique community of practice (CoP) through a SaP partnership, and the collaborative benefits for teaching, learning, and research that developed within this “partnership learning community” over the course of a semester. Analyzing systematic discussion mappings of our meetings, transcripts from those meetings, and personal reflections, we describe our developing roles through sharing and listening to each other. Even though our CoP was set within the space of higher education and grounded by goals of SaP research, this community building partnership, in which members move beyond novice/expert relationships, has implications beyond higher education.